Analysis of a late 19th century french cipher created by Major Josse. Issue 1 (2nd January 2023) - Lasry, George
Abstract: Rémi Géraud-Stewart and David Naccache have recently discovered historical documents from the late 19th century, written by Major H.D. Josse of the French Army, that describe a proposal for a new cipher. In our paper, we provide an in-depth analysis of the cipher and a revised formal description of the cipher based on the examples given by Josse. We also present classes of cryptologically equivalent keys, and a possible attack based on ciphertext isomorphs, that can be implemented with only pen-and-paper. We also describe a new ciphertext-only stochastic attack, based on simulated annealing, that can recover the key and the plaintext from ciphertexts with only 75 letters. We are planning to implement the cipher in CrypTool 2, an e-learning platform for cryptography.